Cytogenetic Effect of two species of Rubia plant (Marrubium sp) on genetic material of the dividing onion (Allium cepa L.) Cells - فوزية مفتاح حمد الجازوي; سميرة فرج محمد بوحجر; فوزية رجب القربولي (African Journal of Advanced Pure and Applied Sciences, 2024)
The object of this study is to investigate the cytotoxicity for aqueous extracts of two species of rubia plant (Marrubium vulgare & Marrubium alysson) using onion plant (Allium cepa L.) as regards its efficiency as a bioassay to measuring chromosome aberrations. Which it was the growing root tip cells were treated with different concentrations of aqueous extract (stock,10-1,10-3) with control for different exposure times (4, 12, 24 hours). We focused on the changes in mitotic index, mitotic chromosomal behaviour and the amount of DNA in treated cells. The obtained results indicate that all aqueous extracts of rubia plant can cause different mitotic changes with approximate degrees of reduction in mitotic index, changes in DNA amount and production of a large number of mitotic abnormalities. These changes depend on concentration and duration of treatment. The obtained abnormalities were grouped in two classes – physiological and clastogenic. The physiological class was the most common one, which included: early condensation, stickiness in chromosomes, C-metaphase, multipolar and laggards and clastogenic class including bridges, chromosome fragmentation and micronucleus. The increase in DNA amount in treated samples is suggested to be a result of the accumulation of treated cells in G2 phase. And blocking them from reaching M phase explains the inhibition of the mitotic index (MI).